Cambian los tiempos, pero ¿cambian las universidades? La educación superior ante los retos de la nueva sociedad - Joan Rué (Universidad de La Rioja, 2013)
Change is the new mot d'ordre in the current international university context in Europe. But, beyond all the institutional statements there is still appropriate to consider this question: Change? What kind of change?. In this paper we shall move along two main perceptions. The first one stresses that everything is moving forwards quickly and the second one underlines the fact that everything in universities tends to remain as it used to be, in its basic trends. In this paper we do stand, whit others, in sharing the changing perspective, specially because it is deeply related to the social forces that push forwards into that direction. Nevertheless, we are aware about the risk that promoted changes can be reduced into a simple institutional making up, unless we understand the nature of the High Education institutions, let's say its cultures, and, according to that, we also succeed in defining the best strategies that fit in such observed conditions and cultures. As a conclusion of the paper the reader will find some main keys that inspire the current process of change developed in the Barcelona Autonomous University (UAB).